VARIATIONS IN MORPHOLOGY OF LEPTOCENTRUS BAJULANS (MEMBRACIDAE : HOMOPTERA) FEEDING ON EIGHT HOST PLANTS - VERMA, SHAVETA; SHARMA, BALDEV (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
Leptocentrus bajulans is a polyphagous membracid species show morphometric variations on eight different host plants i.e Cassia glauca (Lam); Cestrum diurnum (Linn.); Lawsonia alba (Lamk.); Tamarandus indica (Linn); Emblica qfficinalis (Gaertn.); Dalbergia sissoo (Roxb.); Cassia fistula (Linn), Albizzia lebbeck (Benth.); has been observed and incorporated in this paper. These observations were also compared with environmental factors. Observations revealed that female insects in general larger than male irrespective of host plant on which it is feeding. As far as the host value is concerned Cassia fistula is the best host as nearly all the morphometric characteristics show an upward value in the insects feeding on it. Another conclusion is that different host plants result in differential development of various parameter in the individuals of the same species.